Shoes Buying Behaviour of Student - Maskey, Rita (Management Dynamics, 2018)
This paper attempts to examine the shoes buying behavior of students. This study is based on primary data. Only limited tools are used to analyze data. For footwear business owner and shopkeepers it is very important to know the buying behavior of students because they cover a large scale of footwear markets. It helps them to know the brand choice, types of shoes they prefer and price level that student looks before buying the shoes.